2022
DOI: 10.37349/etat.2022.00076
|View full text |Cite
|
Sign up to set email alerts
|

Yeast as a tool to decipher the molecular mechanisms underlying the functions of Bcl-2 family

Abstract: The budding yeast Saccharomyces cerevisiae, a favorite model in biology, does not contain any protein of the Bcl-2 family. From initial experiments with two-hybrid systems to the heterologous expression of human Bcl-2 family members, and the characterization of several forms of yeast programmed cell death, it has however always been a powerful tool to gain information on the mechanisms of apoptosis in general and on Bcl-2 family in particular. This is a short survey of 25 years of experiments that have provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 205 publications
0
6
0
Order By: Relevance
“…Thus, yeasts, as an experimental model system, offer great advantages over other disease models due to the simplicity, short life cycle, low-cost cultivation techniques, relatively simple, cheap, and quick genetic and environmental manipulations, the large knowledge base and data collections, and availability of an unprecedented number of genomic and proteomic toolboxes and high-throughput screening techniques (Figure 1). S. cerevisiae shows a high degree of conservation of different basic biological processes with all eukaryotic cells, such as gene interactions and recombination [57], the regulation of the cell cycle [58], organelle function, energy metabolism [59], mitochondria biogenesis [60], protein folding, quality control and degradation [61], proteostasis network [62], endocytosis [63], secretion [64], vesicular trafficking [65], autophagic pathways [66], programmed cell death [67], and many key signaling pathways, such as mitogen-activated protein kinase (MAPK) [68] and target of rapamycin (TOR) [69]. Moreover, in the majority of cases, these pathways were originally identified and studied in yeasts.…”
Section: Yeast As a Model Of Admentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, yeasts, as an experimental model system, offer great advantages over other disease models due to the simplicity, short life cycle, low-cost cultivation techniques, relatively simple, cheap, and quick genetic and environmental manipulations, the large knowledge base and data collections, and availability of an unprecedented number of genomic and proteomic toolboxes and high-throughput screening techniques (Figure 1). S. cerevisiae shows a high degree of conservation of different basic biological processes with all eukaryotic cells, such as gene interactions and recombination [57], the regulation of the cell cycle [58], organelle function, energy metabolism [59], mitochondria biogenesis [60], protein folding, quality control and degradation [61], proteostasis network [62], endocytosis [63], secretion [64], vesicular trafficking [65], autophagic pathways [66], programmed cell death [67], and many key signaling pathways, such as mitogen-activated protein kinase (MAPK) [68] and target of rapamycin (TOR) [69]. Moreover, in the majority of cases, these pathways were originally identified and studied in yeasts.…”
Section: Yeast As a Model Of Admentioning
confidence: 99%
“…Moreover, in the majority of cases, these pathways were originally identified and studied in yeasts. S. cerevisiae shows a high degree of conservation of different basic biological processes with all eukaryotic cells, such as gene interactions and recombination [57], the regulation of the cell cycle [58], organelle function, energy metabolism [59], mitochondria biogenesis [60], protein folding, quality control and degradation [61], proteostasis network [62], endocytosis [63], secretion [64], vesicular trafficking [65], autophagic pathways [66], programmed cell death [67], and many key signaling pathways, such as mitogen-activated protein kinase (MAPK) [68] and target of rapamycin (TOR) [69]. Moreover, in the majority of cases, these pathways were originally identified and studied in yeasts.…”
Section: Yeast As a Model Of Admentioning
confidence: 99%
“…While several studies report the effect of histone modifications on yeast apoptosis [32], none of them reported the impact of histone modifications on the transcriptional regulation of apoptotic genes. Considering the facts that Aif1‐mediated yeast apoptosis is caspase‐independent [33,34], its gene levels increase upon boric acid or lithium metaborate (two industrially important chemicals) treatment [35], its involvement in yeast apoptosis due to a wide array of molecules, including H 2 O 2 [6], acetic acid [6], manganese [36], an antifungal agent like caspofungin [37] and its role in fluconazole sensitivity [38], studying the AIF1 gene regulation will significantly add to the growing literature of AIF1 mediated effects on yeast cell while providing impetus to the study of the regulation of apoptosis‐related genes.…”
mentioning
confidence: 99%
“…Apoptotic caspases-3 and -7 were found to cleave GSDMD at Asp87( 84 DAMD 87 ), which inactivated the cytotoxic N-terminal domain of GSDMD, and inhibited the subsequent pyroptotic cell death 24,27 .Activation of the necroptotic effectors-Receptor-interacting serine/threonine-protein kinase 3 (RIPK3) and/or Mixed lineage kinase domain-like (MLKL)-by Toll-like receptor (TLR)-or TNFR1-induced signaling pathway, may also induce caspase-1 cleavage of GSDMD via formation of NLRP3 inflammasome 28,29 . Studies focusing on GSDME have revealed that, in cells expressing GSDME, activation of the executioner caspase-3 via either intrinsic or extrinsic apoptotic pathway can cleave and activate GSDME at Asp270 ( 267 DMPD 270 ), which results in pyroptosis 30,31 .Yeast expression has long been used to study mammalian cell death proteins [32][33][34] . Overexpression-mediated activation of cell death effector proteins circumvents the requirements for receptor activation and signal transduction mediated by upstream adaptor proteins in mammalian cells, such that the impact on yeast viability by co-expressed recombinant proteins reflects their interactions and functions in mammalian cells [35][36][37] .…”
mentioning
confidence: 99%
“…Yeast expression has long been used to study mammalian cell death proteins [32][33][34] . Overexpression-mediated activation of cell death effector proteins circumvents the requirements for receptor activation and signal transduction mediated by upstream adaptor proteins in mammalian cells, such that the impact on yeast viability by co-expressed recombinant proteins reflects their interactions and functions in mammalian cells [35][36][37] .…”
mentioning
confidence: 99%